(untitled) (Patan Pragya, 2022)
Due to its numerous health advantages, coriander is one of the most used cooking ingredients. This paper describes the coriander plant’s germination and growth after plasma treatment. The seeds are treated using the gliding arc for periods ranging from one minute to ten minutes. It is discovered that as treatment time is extended, the temperature of the seed rises while its weight continues to fall. The sixth and ninth days are used to calculate the germination rate. The study shows that the treatment time of plasma on seeds increases the hydrophilicity of coriander seeds. It is found that roots and shoots of seeds treated for ten minutes and eight minutes were significantly longer than the other seeds.